Predictive Value of V̇O2peak in Adult Congenital Heart Disease in Comparison With Heart Failure With Reduced Ejection Fraction - Soares, Andrea; Park, Lauren K.; Mansour, Emily; Deych, Elena; Puritz, Alyssa; Zhao, Min; Cao, Chao; Coggan, Andrew R.; Barger, Phillip M.; Foraker, Randi; Racette, Susan B.; Peterson, Linda R. (The American journal of cardiology, 2025)
Peak oxygen consumption (V̇O2peak) is used to predict outcomes and time to transplantation in patients with heart failure with reduced ejection fraction (HFrEF); V̇O2peak also has predictive utility in patients with adult congenital heart disease (ACHD). However, the predictive value of a given V̇O2peak on cardiac events in patients with ACHD compared to HFrEF, especially after adjustment for age and sex, is unclear. Therefore, we performed a longitudinal cohort study comparing patients with ACHD to patients with HFrEF. The cohorts were sex and age matched (±10 years). V̇O2peak tests were conducted from 1993 to 2012. Cardiac events included death, cardiac transplantation, and LVAD placement. Events were obtained via electronic medical record, SSDI, and phone interview. Cox proportional-hazard regression analyses were used to evaluate relationships of event-free survival with predictor variables. Patients with ACHD (N = 137) and HFrEF (N = 137) had median follow-up times of 19.0 years (14.8 to 21.1) and 14.5 years (13.4 to 15.6), respectively. In multivariable models, Higher V̇O2peak was associated with lower risk for a cardiac event, independent of age and sex, in both ACHD (HR 0.89, 95% CI 0.83 to 0.96, p = 0.002) and HFrEF (HR 0.86, 95% CI 0.82 to 0.91, p <0.001). Male sex was associated with greater risk of a cardiac event HFrEF (HR 1.90, 95% CI 1.24 to 2.90, p = 0.003) but not in ACHD group. After multivariable adjustment (Beta-blockers, sex, and V̇O2peak), having ACHD conferred a 71% lower risk of cardiac events compared to a HFrEF diagnosis (HR 0.29, 95% CI 0.18 to 0.47, p <0.001). V̇O2peak independently predicts event-free survival among adults with ACHD or HFrEF and has clinical utility in outpatient settings. Patients with ACHD have a better prognosis after multivariable adjustment including V̇O2peak compared to HFrEF.